Requirements Evolution in Software Product Lines: An Empirical Study - Pereira, Raphael Pereira De; Almeida, Eduardo Santana De (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2015)
The evolution of the requirements specification is a key activity for maintaining the goals of any software project and it has long been established and recognized by researchers and practitioners. Within Software Product Lines (SPL), this evolution is even more critical due to the necessity of dealing with common, variable, and product-specific requirements, not only for a single product but for the whole set of products. In this paper, we present the Feature-Driven Requirements Engineering Evolution (FeDRE2) approach, which provides support to evolve the requirements specification of SPL. The approach evolves the feature model and the use case specification from an SPL according to the user's needs. It also provides detailed guidelines on how to evolve chunks of features from a feature model and their related use case specifications. The evaluation of the approach is illustrated in an empirical study for evolving an SPL of mobile applications for emergency notifications. This empirical study was applied within 16 participants, 9 participants from Federal University of Bahia (Brazil) and 7 participants from Polytechnic University of Valencia (Spain). Evaluations concerning the perceived ease of use, perceived usefulness, effectiveness, and efficiency as regards requirements analysts using the approach are also presented. The results have shown that FeDRE2 was perceived as easy to learn and useful by the participants.